PERAN UMKM (USAHA MIKRO, KECIL, DAN MENENGAH) DALAM PEREKONOMIAN INDONESIA - Sofyan, Syaakir (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
UMKM is a mandate of UUD 1945 which must be realized through national development based on economic democracy. UMKM have an important role in addressing various issues and economic problems of the country, including the fulfillment of community needs for goods/services, unemployment, and employment. In carrying out its role, UMKM still have many difficulties and limitations and have not been able to realize its ability and role maximally in social and economic function. The solution is the full involvement of the government as policy makers, the banking industry as credit providers and the public. All three parties must synergize and play an active role in realizing independent UMKM.